Tautomerism of para-Aminobenzylidene-para-methoxyaniline - Asmaa Baker Aldabbagh (Universitas Islam Indonesia, 2020)
ABSTRACT: In the early seventies received wide attention when Patai [1] published his book tagged the chemistry of the azomethane group and the aforementioned group is very important in the fields of chemistry, life sciences, chemical and pharmaceutical industries and medicine. The chemistry of imines includes two main groups is Schiff bases and oximes. as well as presence of double bonds in the imines facilitated the possibility of their presence in the form of two Geometrical Isomers. Curtin and Husser [2] are among the first to discover the presence of imines in two forms, syn and anti, and the inability to separate these two forms in the imines is attributed to the freedom to rotate around the double bonds between The carbon and nitrogen atoms, which reduce the occurrence of the polarization process in C=N and facilitate the rotation process [3]. Keywords: tautomerism, organic chemistry, azomethane group